(untitled) (Philological Studies, 2020)
The article is devoted to the analysis of the philosophical and religious works of I.A. Krylov, in which there is a motive of man’s “falling away” from nature as a loss of heavenly bliss. At the early stage of his creative work, the poet was looking for various approaches to reflect this existential problem, embodying his thought in images of nature and civilization. These images bear the imprint of the stylistics of two different genres of Russian classicism: odes (high style) and idyll (middle style). Stylistic and genre analysis makes it possible to reveal Krylov’s attitude to the world as a whole and to a person’s place in it. Idyllic elements are associated with the notion of primordial innocence. The high style of the ode manifests itself in two ways: in threatening prophetic denunciations and solemn praises. The solemn praise of nature is in tune with the chanting of the Creator in the Psalm arrangements – the traditional genre of Russian classicism. Based on these parallels, we can assume the development of the poet’s philosophical search from rejection of civilization to the organic reunion of man with being through the creative principle.